2006
DOI: 10.1089/ten.2006.12.1565
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Microstructural Characteristics of a Collagen Film-Based Corneal Stroma Equivalent

Abstract: The growth in refractive surgeries and corneal replacements has fueled interest in the development of a tissue-engineered cornea. This study characterizes the microstructure and biomechanical properties of film-based corneal stroma equivalents over time in culture. The increased collagen density in the films was hypothesized to result in improved mechanical properties both initially and over time. The microstructure of the film-based stromal equivalent was examined using atomic force microscopy and scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Our tension results indicate good agreement with previous studies that demonstrated a significant decrease in mechanical properties Representative DSC thermograms of MD (a) and DM (b) in either the dry or rehydrated state of collagen matrices going from the dry to the wet state [18,19]. The present study did not determine the specific mechanism for the change in mechanical properties following rehydration of the different collagen matrices.…”
Section: Discussionsupporting
confidence: 92%
“…Our tension results indicate good agreement with previous studies that demonstrated a significant decrease in mechanical properties Representative DSC thermograms of MD (a) and DM (b) in either the dry or rehydrated state of collagen matrices going from the dry to the wet state [18,19]. The present study did not determine the specific mechanism for the change in mechanical properties following rehydration of the different collagen matrices.…”
Section: Discussionsupporting
confidence: 92%
“…The initial relaxed modulus was 0.03 MPa for collagen sponges and 2.1 MPa for single collagen films. 12 In contrast, the modulus of collagen gels is in the range of 1.4-24.3 kPa and dependent on the concentration of collagen during at the start of gelation which was from 0.3 to 3 mg/mL of collagen in studies by Roeder et al 47 The modulus of the collagen sponge used in this investigation is lower than that of the collagen films. The difference in fibril diameter synthesized on the collagen sponge may reflect the influence of both compaction and microstructure.…”
Section: Fibril Diameter and Distributionmentioning
confidence: 60%
“…Collagen sponges formed from freeze-drying and crosslinking a dispersion of insoluble collagen had both a modulus and ultimate tensile strength (UTS) of 0.03 MPa, and modification of the matrix manufacturing method resulted in the formation of a collagen film with a relaxed modulus and UTS of 2.1 MPa and 1.6 MPa respectively. 12 These mechanical properties are considerably higher than those observed in a collagen gel (modulus 1.4-24.3 kPa for 0.3-3 mg/mL collagen 47 ). The properties of the matrix can change with time in culture as seen with a decline in the modulus for both collagen sponges 5,40 and collagen films.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations